Virtual reality smartphone-based intervention for smoking cessation : pilot randomized controlled trial on initial clinical efficacy and adherence - Goldenhersch, Emilio (2020)
This study aimed to evaluate participant adherence and smoking cessation outcomes in a pilot randomized controlled trial of the digital intervention Mindcotine (MindCotine Inc) using a self-administered treatment of virtual reality combined with mindfulness.